Appropriation Art. On what we might call fordamnative appropriations - Matos Trindade, Carlos Alberto (2023)
In a 1992 essay, Benjamin Buchloh considered Robert Rauschenberg's famous Erased De Kooning Drawing (1953) to be the first inaugurating gesture and emblem of the postmodern appropriationist act. For our part, we believe that his gesture should be distinguished from current appropriationist practices, and in this article we propose the concept of fordamnative appropriation to classify it, as well as other subsequent gestures by other artists who can invoke his example, and which we analyse below. Before this analysis, we will introduce the emergence and development of Appropriation Art, which arose in the context of what is known as postmodernism, as well as mentioning some of the historical antecedents of this artistic practice; in addition, in order to contextualise the concept we have introduced and the analysis that follows, we address the origins and use of the Latin phrase damnatio memoriae, from ancient Roman civilisation to modern and contemporary politics.